The effects of walking posture on affective and physiological states during stress - Hackford, Jessie; Mackey, Anna; Broadbent, Elizabeth (Journal of behavior therapy and experimental psychiatry, 2019)
Embodiment theory proposes that motor processes are associated with emotions and cognitions. Previous research has shown that walking posture can influence affective memory bias. This study further investigated this theory by looking at the effects of an upright versus slumped walking posture on psychological and physiological states when faced with a psychological stressor. Seventy-three healthy adults completed baseline self-report measures of affect, power, and sleepiness, and physiological measures of blood pressure, galvanic skin response, and skin temperature. After walking in their usual posture, the same self-report and physiological measures were obtained. Participants were then randomly allocated into one of two groups where they were asked to walk in either an upright posture or a slumped posture. While walking, participants underwent a psychological stressor. After experimental walking, the same self-report and physiological measures were obtained. The upright walking posture group showed significantly improved psychological states including less low arousal negative affect, less sleepiness, less pain and marginally greater feelings of power than the slumped walking posture group. Physiologically, the upright walking posture group showed significantly lower systolic blood pressure, galvanic skin response, and marginally lower skin temperature than the slumped walking posture group. This was a short-term laboratory-based experiment and results may not generalise to other situations. Walking posture can affect both psychological and physiological states. Applications of these findings may have implications for improving mental and physiological health. •An experimentally altered walking style impacted psychological states during stress.•Walking style also impacted physiological states during stress.•Changing the way a person walks may improve their responses to stress.